Bagasse fired power plant with carbon dioxide recovery a plant design - Guevara, Rafael Jose; Ong, Jaypee; Toledo, Ranel Irvin
The feasibility of power production in Mindanao using sugarcane bagasse was studied in this paper. This plant design study covers the design process of the whole power plant generation and the accompanying equipment requirements and utilities needed. The economics related to this production and operations of a power plant to serve this purpose were also analyzed through profitability and sensitivity analyses. The proposed power plant has an installed capacity of 40 MW and uses bagasse biomass as the main fuel for the gasification process. This is co-generated with 36 tons of carbon dioxide recovery per day. These were derived using the estimated 1.4 million tonnes per year of bagasse available for power generation. Operations are continuous and will be operate for 330 days per year. The 200 meter x 100 meter site is in Maramag City, Bukidnon, Northern Mindanao near the Crystal Sugar Mill and along the delta of Pulangi River. Bagasse is first prepared by removing its moisture content. It is then pelletized, and conveyed into a circulating fluidizing bed gasifier in which synthesis gas or syngas is produced. The other chamber within the unit will be used for methanation - wherein the syngas is further processed and converted into steam. The steam from these units is then used to drive a boiler turbine system wherein mechanical energy is converted into electrical energy. Carbon dioxide is then recovered from the gasification process and purified by passing it through absorbers, strippers and scrubbers until it is finally liquefied and stored. Electricity generated will be priced around PHP 3.30 per kWh as compared to the increasing price of electricity generated in Mindanao, which was at PHP 3 per kWh as of May 2012. Carbon dioxide will be sold at Php 22.50 per kilogram following the standard prices for the gas in liquid form. Factoring in all the expenses for equipment purchase, utilities and other expenses, a fixed capital investment of at least PHP 4.220 billion is required to build the plant. It is projected to have a net present value of PHP 17.49 billion after its 20-year plant life with a 25 percent Internal Rate of Return. The plant is expected to earn after 4-5 years of operation. Through the synthesis of the market needs in Mindanao, the detailed development of equipment needed to achieve the desire processes through a profitability analysis of the entire plant, it can be concluded that the power generation through gasification of sugarcane bagasse is feasible and profitable.